Chemical Composition and Bioactive Antioxidants Obtained by Microwave-Assisted Extraction of Cyperus esculentus L. By-products: A Valorization Approach - Pelegrín, Carlos Javier; Ramos, Marina; Jiménez, Alfonso; Garrigós, María Carmen (Frontiers in Nutrition, 2022)
Tiger nut is highly appreciated in the Mediterranean basin by the large number of nutritional advantages offered by a beverage, called "horchata”, which is directly obtained from the tuber of Cyperus esculentus L. However, the current tiger nut harvesting and processing practices generate a large number of residues, mainly the plant that remains in the fields. In this work the plant residues have been fully characterized to get a clear picture of the possibilities for its valorization. Several analytical techniques have been applied to obtain data to assess the real possibilities of these residues in applications in the food and nutrition sectors. Results on the compositional and elemental analysis, monosaccharide composition, phenolic concentration and antioxidant capacity were obtained from the dry plant. The high content of α-cellulose (47.2 ± 1.8%) in DP could open new possibilities as raw material in the production of cellulose nanoentities. Many essential minerals with nutritional interest and free sugars were identified making it an interesting source of valuable nutrients. The total carbohydrate content was 171 ± 31 mg gdm-1. Microwave-assisted extraction was used to obtain extracts rich in polyphenols. A Box–Behnken design was used, and the optimal extraction conditions were 80 °C, 18 min, ethanol concentration 40% (v/v), and solvent volume 77 mL, showing extraction yield of 2.27 ± 0.09%, TPC value 136 ± 3 mgGAE 100 gdm-1 and antioxidant capacity 8.41 ± 0.09 µmolTrolox gdm-1. Other assays (FRAP and DPPH) were also tested, confirming the high antioxidant capacity of DP extracts. Some polyphenols were identified and quantified: p-coumaric (7.67 ± 0.16 mg 100 gdm-1), ferulic (4.07 ± 0.01 mg 100 gdm-1), sinapinic (0.50 ± 0.01 mg 100 gdm-1) and cinnamic acids (1.10 ± 0.03 mg 100 gdm-1), 4-hydroxybenzaldehyde (1.28 ± 0.06 mg 100 gdm-1), luteolin (1.03 ± 0.01 mg 100 gdm-1) and naringenin (0.60 ± 0.01 mg 100 gdm-1). It can be concluded that Cyperus esculentus L residues obtained from the tiger nut harvesting and horchata processing could be an important source of high value compounds with potential uses in different industrial sectors, while limiting the environmental hazards associated with the current agricultural practices.